The politics of Amazonian deforestation: environmental policy and climate change knowledge. (1st July 2014) - Monteiro, Marko S. A.; Seixas, Sonia Regina da Cal; Vieira, Simone Aparecida
Abstract : This article reviews literature on the science and politics of deforestation in the Amazon from 1970 until today, focusing on their shifting meanings and the increasing relevance of climate change knowledge to their understanding and management. Since large‐scale colonization of the region began in the 1970s, the debate on deforestation has been crucial in disputes involving science, development, and the environment. In the last decade, the issue of climate change has become more present in the science, politics, and policies related to deforestation in the Amazon. This debate has helped shift discussions on both the environmental and the development agenda for the region. Although there is a broad agreement that the Amazon is being increasingly integrated into global fluxes of knowledge, goods, and people, not all view this process under the same light. The review concludes that scientific views help condition the development of changing policy arrangements aimed at curbing deforestation, and the incorporation of climate change knowledge is an important aspect of the dynamics of environmental policies in the region. WIREs Clim Change 2014, 5:689–701. doi: 10.1002/wcc.298 This article is categorized under: Social Status of Climate Change Knowledge > Knowledge and Practice